2015
DOI: 10.3892/etm.2015.2776
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of paeoniflorin against FasL-induced apoptosis of intervertebral disc annulus fibrosus cells via Fas-FasL signalling pathway

Abstract: Abstract. In the present study, we demonstrate that the degeneration of intervertebral discs is caused by ageing and apoptosis of matrix cells. Apoptosis is as essential as the function of proteoglycan synthesis in assessing the possible degeneration of intervertebral discs; paeoniflorin (PF) induces cytoprotective effects on various types of cells. In this study, the function of PF in inhibiting Fas ligand (FasL)-induced apoptosis in annulus fibrosus cells was assessed, and the correlation between apoptosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Fas ligand (FasL), a member of the tumor necrosis factor family, is a type-II transmembrane protein that can induce cell apoptosis [7]. FasL-induced apoptosis also plays essential roles in the development of IDD [8]. In effect, inhibition of FasL provides new insights into the treatment of IDD [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fas ligand (FasL), a member of the tumor necrosis factor family, is a type-II transmembrane protein that can induce cell apoptosis [7]. FasL-induced apoptosis also plays essential roles in the development of IDD [8]. In effect, inhibition of FasL provides new insights into the treatment of IDD [9].…”
Section: Introductionmentioning
confidence: 99%
“…In an adjuvant-induced arthritis model, paeoniflorin inhibited the expression of IL-1β, IL-6, IL-17, and TNF-α and upregulated the production of TGF-β1 (8). In other musculoskeletal systems, Chen et al (9) demonstrated that paeoniflorin could block the apoptosis of fiber ring cells by reducing the expression of Fas and caspase-3 proteins via regulation of Fas-FasL signaling. Moreover, in internal disc disruption disease, paeoniflorin was also reported to decrease the percentage of dead nucleus pulposus cells by inhibiting the activation of caspase-3 and -9 and increasing Bcl-2 family protein expression (10).…”
Section: Introductionmentioning
confidence: 99%
“…Fas, FasL and caspase-3 are the important proteins mediating the apoptosis of cells. At present, it has been found that FasL could be induced by certain stress responses, such as ultraviolet and DNA damage, and the interactions between FasL and Fas could induce programmed death of cells, which may be an important mechanism of the body to clear cells having mutation [ 27 ]. FasL could express on the surface of tumor cells, and tumor-specific antigen could induce tumor infiltrating T lymphocytes (TIL) to express Fas in large quantity, it enhances the sensibility of T cells to apoptosis.…”
Section: Discussionmentioning
confidence: 99%